STRATEGI GURU PAI DALAM MENINGKATKAN RELIGIUSITAS SISWA MELALUI PENERAPAN NILAI-NILAI AGAMA ISLAM PADA SISWA SMPN 2 SUMBERASIH PROBOLINGGO - Setiawati, Tanti; Nuha, Nazaha Ulin (LPPM STAI Muhammadiyah Probolinggo, 2023)
This resarch has an important objective, namely to find an overview of the strategies of Islamic Religious Education teachers in increasin student religiosity at SMPN 2 Sumberasih, Probolinggo Regency. This research uses qualitative research or field studies with the main source reffering to PAI teachers in strategies to increase students’ religiosity scores at the school. Data collection techniques in this research used the stages of observation, interviews, documentation, analysis and drawing conclusions. Researchers also concluded that the PAI teacher at SMPN 2 Sumberasih, Probolinggo Regency has the following strategy; The first provide examples of good morals to students every day. The second guide students in every activity so that students can receive a positive impact in every religious activity carried out. And third Encourage students to carry out and practice raligious habits implemented at school. The methods used by PAI teachers in implementing strategies to increase students’ religious values use the methods of inspiration, habitutaion, sanctions and rewards. This really helps the effectiveness of religious activities at school. Keywords: Strategy; Teachers, Students; Religiosity.